Generation of low-frequency oscillations in the subsolar venus ionopause - Singh R.N.; Upadhyay H.O. (My University, 2025)
The steep electron density gradient, the magnetic field curvature and the effect of gravity make the Venus ionopause region unstable. The onset of flute instability in the Venus ionopause plasma has been studied. The dispersion of waves and their growth have been studied using in situ measured data. The existence of low frequency waves in the subsolar magnetic field data ionopause region has been interpreted to arise as the result of flute instability. © 1989 Indian Academy of Sciences.